2020
DOI: 10.1002/lpor.202000319
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Ratiometric Luminescence Thermometry Based on Thermally Coupled Levels for Bioapplications

Abstract: Noninvasive lanthanide‐doped optical thermometers based on fluorescent intensity ratio (FIR) technique have emerged as promising noncontact tools for detecting the inaccessible objects at different scales. Currently, the theoretical and experimental investigations of various influential factors on thermal performances of luminescence thermometers have become one of the hotspots to develop highly sensitive optical thermometers. On the other hand, near‐infrared (NIR) light‐responsive nanothermometers with deep‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
173
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(176 citation statements)
references
References 179 publications
(150 reference statements)
2
173
0
1
Order By: Relevance
“…However, in the case of Eu 3+ , the thermally coupled populations of the levels 7 F 0 and 7 F 1 should be considered once their populations were the starting point when the energy transfer occurs. [51] Level Population Analysis: After all rates involved in the complexes were determined, the level population kinetics was described by a set of ordinary differential equations, [72,82,94] = ∑ − ∑ = → = → 1 1 dP dt W P W P i j j i j j i j i (7) where the summations run all levels of the system. P i and P j are the populations of the levels |i〉 and |j〉, the W j→i and W i→j are the energy transfer rates between these states.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of Eu 3+ , the thermally coupled populations of the levels 7 F 0 and 7 F 1 should be considered once their populations were the starting point when the energy transfer occurs. [51] Level Population Analysis: After all rates involved in the complexes were determined, the level population kinetics was described by a set of ordinary differential equations, [72,82,94] = ∑ − ∑ = → = → 1 1 dP dt W P W P i j j i j j i j i (7) where the summations run all levels of the system. P i and P j are the populations of the levels |i〉 and |j〉, the W j→i and W i→j are the energy transfer rates between these states.…”
Section: Methodsmentioning
confidence: 99%
“…
The main reason behind the impressive blow-up that occurred in the middle of the last decade [2] was the popularization of light-emitting micro and nanomaterials allowing remote temperature sensing detection at scales below 1 micron, where the traditional thermometers (e.g., thermocouples and pyrometers) are generally unsuitable. [3][4][5][6][7] The impact of luminescence thermometry has been felt, therefore, in disparate areas, such as biomedicine [8][9][10] (including in vivo [11,12] and in vitro [13,14] sensing), catalysis, [15,16] microelectronics, [17][18][19] Internet of Things, [20] magnetism, [21][22][23][24] vacuum sensing, [25] and microfluidics. [26] Indeed, thermographic phosphor thermometry was compared with radiation and contact thermometry in an industrial setting and the results proved that the approach is an effective alternative to conventional techniques offering better performance.
…”
mentioning
confidence: 99%
“…Up to date, it has been confirmed that ten kinds of rare earth ions have at least one pair of TCELs. [ 8–10 ] Among these TCELs, the 2 H 11/2 / 4 S 3/2 energy levels of erbium(III) ion (Er 3+ ) has attracted much attention due to its moderate energy difference (△ E ≈ 800 cm −1 ) and efficient green emission. [ 11 ] Perovskite composite materials are a large class of compounds with the same structure as the chemical formula ABO 3 of CaTiO 3.…”
Section: Introductionmentioning
confidence: 99%
“…[ 35,36 ] The current interest in luminescence thermometry is well evidenced in a series of very recent review papers. [ 26,37–42 ] Luminescence is a noninvasive spectroscopic method for temperature measurement based on the thermal dependence of the phosphor emission (also known as the thermometric parameter) combining high relative thermal sensitivity ( S r > 1%K −1 ) and spatial resolution (10 −6 m) with short acquisition times (<10 −3 s). [ 26,35,36,43–48 ] The working principle of luminescence thermometry is based on the temperature dependence of the materials’ emission that manifests itself mostly through the 1) variation in the lifetime of a certain excited energy level, 2) emission peak shift or, the most used 3) variation in the emission intensity ( I ) of one or two electronic ( I 1 and I 2 ) transitions, Figure .…”
Section: Optical Temperature Sensors Overviewmentioning
confidence: 99%